x1 = -re(acos(-3)) + 2*pi - i*im(acos(-3))
x2 = 2*pi - i*im(acos(4))
x3 = re(acos(-3)) + i*im(acos(-3))
x4 = re(acos(4)) + i*im(acos(4))
Объяснение:
x1 = -re(acos(-3)) + 2*pi - i*im(acos(-3))
x2 = 2*pi - i*im(acos(4))
x3 = re(acos(-3)) + i*im(acos(-3))
x4 = re(acos(4)) + i*im(acos(4))
x1 = 3.14159265358979 + 1.76274717403909*i
x2 = 6.28318530717959 - 2.06343706889556*i
x3 = 3.14159265358979 - 1.76274717403909*i
x4 = 2.06343706889556*i
сумма
-re(acos(-3)) + 2*pi - i*im(acos(-3)) + 2*pi - i*im(acos(4)) + i*im(acos(-3)) + re(acos(-3)) + i*im(acos(4)) + re(acos(4))
=
4*pi + re(acos(4))
произведение
(((-re(acos(-3)) + 2*pi - i*im(acos(-3)))*(2*pi - i*im(acos(4*(i*im(acos(-3)) + re(acos(-3*(i*im(acos(4)) + re(acos(4)))
=
-(2*pi - i*im(acos(4)))*(i*im(acos(-3)) + re(acos(-3)))*(i*im(acos(4)) + re(acos(4)))*(-2*pi + i*im(acos(-3)) + re(acos(-3)))
X^2 + 6X = 6 + 5X
X^2 + X - 6 = 0
D = 1 + 24 = 25 ; √ D = 5
X1 = ( - 1 + 5 ) : 2 = 2 ( не подходит)
X2 = ( - 6) : 2 = ( - 3 )
ОТВЕТ Х = ( - 3 )
ЗАДАЧА 2
1) 96 : 3 = 32 ( км/час ) скорость удаления
2) Х ( км/час) скорость первого катера
( Х - 10) км/час скорость 2-го
Х + Х - 10 = 32
2Х = 42
Х = 21 ( км/час) скорость первого
ОТВЕТ 21 км/час